Pengaruh candesartan cilexetil pada aliran darah otak penderita stroke dengan hipertensi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Stroke is recognized as a devasting and important neurological disorder. Several conditions and lifestyle factors have been identified as risk factors for stroke, these include hypertension. Hypertension is the most prevalent and modifiable risk factors for stroke, and its treatment subtantially reduces the risk of stroke. Treatment with antihypretensive medications is useful to decrease stroke morbidity and mortality. Candesartan cilexetil is a new, once daily oral antihypertensive, which is completely hydrolysed to candesartan, a potent long acting AIIRA selective for the type 1 receptor subtype. Candesartan cilexetil is effective and well tolerated when used once daily, as monotherapy or in combination with other antihipertensive agents, in patients with mild, moderate or severe hypertension. Preclinical data suggest that candesartan cilexetil has a protective effects against stroke. The clinical study involving patients with hypertension, candesartan cilexetil 2-8 mg once daily for 8 weeks maintained cerebral blood flow despite reducing systolic and diastolic blood pressure.